2014
DOI: 10.1128/cvi.00214-14
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream Infections Are an Improbable Cause of Positive Serum (1,3)-β-d-Glucan in Hematology Patients

Abstract: c Ninety-one serum samples from 51 hematology patients with bacteremia infections were tested for (1,3)-␤-D-glucan (BG). Eleven samples (15%) from 7 patients (14%) were positive for BG. Of these 7 patients with positive BG results, 4 (8%) had invasive aspergillosis and 3 (6%) had no invasive fungal disease. Bacteremia was an unlikely cause of the false-positive BG results.A major cell wall component of various clinically important fungi is (1,3)-␤-D-glucan (BG). Serum levels of BG are included in the updated E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Several factors that may increase BDG levels for reasons other than invasive fungal infection have been identified [12], including hemodialysis with cellulose membranes, thrombocyte infusion with leukocyte-removing filters, the administration of human blood products (immunoglobulins or albumins), the use of antibiotics such as amoxicillin-clavulanate or piperacillin-tazobactam [31,32], the presence of serious bacterial infections [12,33], the use of surgical gauzes containing glucan, and severe mucositis [11] and possibly enteral nutrition for their BDG content. Recent studies have also shown that BDG levels are not affected by the use of antibiotics, such as ampicillin-sulbactam and piperacillin-tazobactam [32,34] or the presence of Grampositive bacteremia (in hematology patients) [35,36]. colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors that may increase BDG levels for reasons other than invasive fungal infection have been identified [12], including hemodialysis with cellulose membranes, thrombocyte infusion with leukocyte-removing filters, the administration of human blood products (immunoglobulins or albumins), the use of antibiotics such as amoxicillin-clavulanate or piperacillin-tazobactam [31,32], the presence of serious bacterial infections [12,33], the use of surgical gauzes containing glucan, and severe mucositis [11] and possibly enteral nutrition for their BDG content. Recent studies have also shown that BDG levels are not affected by the use of antibiotics, such as ampicillin-sulbactam and piperacillin-tazobactam [32,34] or the presence of Grampositive bacteremia (in hematology patients) [35,36]. colonization.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of factors reported that may lead to false-positive results of the BDG assay, such as severe mucositis (19), the administration of albumin and immunoglobulins (20), thrombocyte infusion with leukocyte-removing filters, or the administration of antibiotics, such as amoxicillin-clavulanate or piperacillin-tazobactam (6). Although some authors argue that bacteremia is an improbable cause of a positive BDG assay (21), one recent study found a significant higher rate of false-positive BDG tests in bacteremic patients, independently of Gram-positive or Gram-negative bacteremia (6). Importantly, transient candidemia has been reported as a cause of persistent false-positive BDG levels (22), a True-positive (TP) and false-negative (FN) results refer to all BDG values assessed at the time of the potential onset of IFD (e.g., four, two, and zero weeks prior to the first pathological sign, such as blood culture results or biopsy, pathological imaging, or galactomannan positivity); all subsequent levels of BDG were considered a response control for therapy and were not included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Another category of iatrogenic patient contamination, one that has had significant debate, is that of parenteral administration of potentially contaminated antibiotics. Multiple publications asserting the occurrence of patient false positives by this route as well as the opposite have been presented [ 67 , 68 , 69 ]. While this route of patient contamination is possible, the high level of dilution generated upon injection of relatively low volumes of antibiotic make this unlikely.…”
Section: Major Sources Of Circulating Bdgmentioning
confidence: 99%